2011
DOI: 10.1159/000329668
|View full text |Cite
|
Sign up to set email alerts
|

Familial Autosomal Recessive Renal Tubular Acidosis: Importance of Early Diagnosis

Abstract: Background and Aims: Untreated renal tubular acidosis (RTA) can result in severe complications. We reviewed the clinical features of patients with mutations in two genes causing RTA and evaluated their developmental expression assuming that timing, symptom severity and complications may be related to its occurrence. Methods: Clinical data from 16 patients with RTA due to mutations in either ATP6V1B1 or CAII were retrospectively reviewed. Both genes’ localization and expression pattern in the developing human k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…Another inherited disorder associated with hypokalemia and hypercalciuria is distal renal tubular acidosis (dRTA). Several genes are known to cause dRTA, which all affect the ability of intercalated cells in the collecting duct to secrete protons (35,65). Again, polyuria/ polydipsia is a common symptom of this disease, and there are some case reports documenting associated NDI (10, 23), but no systematic data collection of urinary concentrating ability in these patients exists.…”
Section: Inherited Diseases Associated With Sndimentioning
confidence: 99%
“…Another inherited disorder associated with hypokalemia and hypercalciuria is distal renal tubular acidosis (dRTA). Several genes are known to cause dRTA, which all affect the ability of intercalated cells in the collecting duct to secrete protons (35,65). Again, polyuria/ polydipsia is a common symptom of this disease, and there are some case reports documenting associated NDI (10, 23), but no systematic data collection of urinary concentrating ability in these patients exists.…”
Section: Inherited Diseases Associated With Sndimentioning
confidence: 99%
“…In some cases, NC provides a clue to an underlying genetic disorder such as hyperoxaluria or distal renal tubular acidosis with or without deafness [2, 3]. In other cases, NC is a side effect of chronic treatment with various drugs, including loop diuretics and vitamin D. In general, the pathogenesis of NC has not been adequately elucidated, although hypercalciuria appears to be a common finding.…”
Section: Introductionmentioning
confidence: 99%
“…The p.Pro346Arg mutation was previously detected in one patient among 62 studied kindreds of Turkish, Spanish, Saudi Arabian, North American, Pakistani, and European origin (5). A recent study found this mutation in patients from various ethnic groups suggesting to be a common pan‐ethnic mutation (14).…”
Section: Discussionmentioning
confidence: 89%
“…Mutations in ATP6V1B1 gene cause dRTA with or without SNHL (Table S3) (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). The majority of these mutations are missense or nonsense mutations.…”
Section: Discussionmentioning
confidence: 99%